International law and its response to modern security threats that stem from developments in weaponry and technology - Ibragimov, Zh.I.; Assanova, T.S. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2023)
The emergence of new technologies such as nanoteachnology, cybertechnology, outer space and unmanned systems and its rapid development have had an impact on the existing rules of international law, and vice versa, due to advances in technology of weaponry. Handling such situations by law goes through interpretation by the ‘old’ international law and application to a new situation, or if necessary via the enactment of new law. In some cases, existing international law might be applicable to it by the extension of as the appropriate reinterpretation of international conventional norms as customary international law counterparts. Despite the fact that some international laws have been adopted during times of reduced development of technologies and weaponry types, they are nevertheless still likely to be applicable to the challenges and issues of security threats. Given the examples of using chemical weapons and cyber-attacks, this can be considered evidence of weaknesses of some international law norms due to interpretation issues as necessity to strength existing law through application of customary international law rules. Therefore, it is difficult to state that international law is unable to secure peace or help to avoid the threats inherent to new technology and weapons development because of states practice and the contribution of academics.